Treatment seeking behaviour and government primary health care utilisation among male civil servants in Kelantan - Arumugam, Pathman (2020)
Background: Treatment seeking behaviour (TSB) is a sequence of remedial actions which are influenced by many factors that individuals undertake to rectify perceived ill-health. Currently, very little is known regarding TSB among men in Kelantan and their experiences towards primary healthcare utilisation (PHC) in the country especially among civil servants who are considered the largest consumers of public healthcare in Malaysia. Objectives: This study was conducted among male civil servants in Kelantan to determine the TSB and its associated factors and to explore the experiences on PHC services and TSB. Methodology: This was a concurrent parallel mixed method study which consisted of a quantitative and a qualitative part done among male civil servants in Kelantan. By using simple random sampling, a total of 402 participants were involved in the quantitative part of the study using a TSB questionnaire while the second part of the study was conducted by 6 focus group discussions. Descriptive analysis and logistic regression were performed to identify the proportion of inappropriate TSB and the factors associated with inappropriate TSB among male civil servants in Kelantan. A thematic analysis was done in the qualitative part to identify themes. Results: The proportion of inappropriate TSB among male civil servants in Kelantan was 64.6%. There were 12 significant variables identified from the seven models developed using multiple logistic regression which were associated with inappropriate TSB. They were non-Muslims (OR 2.6; 95% CI: 1.1,6.7 p= 0.041), high household income (OR 4.5; 95% CI: 1.7, 11.6 p= 0.022), married (OR 0.3; 95% CI: 0.1, 0.7 p=0.035), average assessment of illness severity (OR 0.45; 95% CI: 0.3,0.7 p=<0.001), low information about illness (OR 3.3; 95% CI:1.4, 7.8 p= 0.012), never received appropriate treatment (OR 5.4, 95% CI: 1.0, 29.5 p= 0.042), importance of cost of treatment (OR 0.2; 95% CI: 0.1, 0.4 p= <0.001), never accepting illness when having symptoms (OR 2.8; 95% CI: 0.9, 8.8 p=0.041), embarassesment expressing illness (OR 0.2; 95% CI: 0.1, 0.5 p= <0.001), much job and family responsibilities as barriers (OR 0.3; 95% CI: 0.1, 0.6 p=<0.001), easy access to medications (OR 0.4; 95% CI: 0.2, 0.7 p=0.011) and affordability as a determinant (OR 0.3; 95% CI: 0.1, 0.6 p= <0.001). Main themes which emerged from the FGD sessions were health literacy, stage of seeking treatment, self-treatment, utilization of services, privacy and attitude of healthcare workers. Conclusions: TSB among male civil servants in Kelantan was poor and factors contributing towards it were multidimensional such as socio-demographic, individual, healthcare provider, psychological, marketing, situational and socio-cultural and family factors. Collaboration is needed from all major stakeholders to improve men’s behaviour to seek treatment and increase their uptake of health services to ensure optimum health in men.